An ultra-high dose of electron radiation response of Germanium Flat Fiber and TLD-100. (January 2017) - Alawiah, A.; Amin, Y.M.; Abdul-Rashid, H.A.; Abdullah, W.S. Wan; Maah, M.J.; Bradley, D.A.
Abstract: The thermoluminescence (TL) response of Germanium Flat Fiber (GFF) and TLD-100 irradiated with 2.5 MeV electrons for the doses up to 1 MGy were studied and compared. The aim was to evaluate the TL supralinearity response at an ultra-high dose (UHD) range and to investigate the change in kinetic parameters of the glow peaks, as the doses increases up to 1 MGy. It is found that the critical dose limit (CDL) of GFF is 5 times higher as compared to TLD-100. CDL is determined by the dose at the maximum supralinearity, f(D) max . It is also found that annealing the TLD-100 and GFF with temperature more than 400 °C is required to reset it back to its original condition, following radiation doses up to 1 MGy. It is also noticed the strange behavior of Peak 4 (TLD-100), which tends to be invisible at the lower dose (<10 kGy) and starts to be appeared at the critical dose limit of 10 kGy. This result might be an important clue to understand the behavior of TLD-100 at extremely high dose range. For both samples, it is observed that the TL intensity is not saturated within the UHD range studied. Highlights: The supralinearity of GFF and TLD-100 was highly dependent on the UHD. The maximum supralinearity f(D)max of TLD-100, occurs around 10 kGy. TL kinetic model can be used to explain the glow peak behavior of doses < f(D)max. The supralinearity response decreases for doses above the critical dose limit.